Integrated mental health care in a multidisciplinary maternal and child health service in the community: the findings from the Suzaka trial - Yoshiyuki Tachibana; Noriaki Koizumi; Chikako Akanuma; Hiromi Tarui; Eizaburo Ishii; Tomomi Hoshina; Ayuko Suzuki; Akiko Asano; Shiho Sekino; Hiroto Ito (BMC, 2019)
Abstract Background Perinatal mental health problems such as mood disorders are common. We propose a new multidisciplinary health service intervention program providing continuous support to women and their children from the start of pregnancy till after childbirth. The aim of this study was to examine the effects of the program with respect to making women's mental health better in the postpartum period and improving the state of care for women and their children in the perinatal period. Methods We performed a controlled study to investigate the effectiveness of the program in Suzaka City, Japan. The women's mental health status was assessed using the Edinburgh Postnatal Depression Scale (EPDS) 3 months postpartum. Of 349 women, 210 were allocated to the intervention group and 139 to the control group. From April 2014 to March 2015, the number of the pregnant women who were followed-up by the multidisciplinary meeting in the intervention and control groups were 60 and 4, respectively. In the same period, the number of the pregnant women who were identified as requiring intensive care were 21 and 2, respectively. Results The total EPDS score, which was the primary outcome of the present study, differed significantly between the intervention and control groups (Mean [SD] = 2.74 (2.89) and 4.58 [2.62], respectively; p < 0.001). The number of the women receiving counseling from a public health nurse (5.3% in intervention group, 0.7% in control group, p = 0.02), attending maternal seminars (attendant ratio: 46% whereas 16%, p = 0.01), and receiving home visits by public health nurses (home visit ratio: 93.8% whereas 82.6%, p < 0.001) was significantly higher in the intervention group compared to the control group. Conclusions The present study indicates that continuum support provided by integrated mental health care through a multidisciplinary maternal and child health service in the community can make women's mental health better in the postpartum period and help women and their children receive more health services from public health nurses. Trial registration Name of registry: Research for the effectiveness of a multi-professional health service intervention program of continuum supports for mother and child which starts for pregnancy periods to enhance maternal mental health. UMIN Clinical Trials Registry number: UMIN000032424. Registration date: April 29th, 2018. Registration timing: retrospective.